1999
DOI: 10.1042/bj3410839
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and activation of phosphodiesterase type 3B (PDE3B) in adipocytes in response to serine/threonine phosphatase inhibitors: deactivation of PDE3B in vitro by protein phosphatase type 2A

Abstract: Phosphodiesterase type 3B (PDE3B) has been shown to be activated and phosphorylated in response to insulin and hormones that increase cAMP. In order to study serine\threonine protein phosphatases involved in the regulation of rat adipocyte PDE3B, we investigated the phosphorylation and activation of PDE3B in i o in response to phosphatase inhibitors and the dephosphorylation and deactivation of PDE3B in itro by phosphatases purified from rat adipocyte homogenates. Okadaic acid and calyculin A induced dose-and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…We used 12B2 to examine the regulation of GSK3β by protein phosphatases in cells. We treated HEK cells for 30 min with 10 nM calyculin A, a potent protein phosphatase inhibitor (Ishihara et al, 1989; Resjo et al, 1999), which increases S9 phosphorylation in GSK3β (Morfini et al, 2004; Kim et al, 2009; Xiao et al, 2010). The cell lysates were analyzed in sandwich ELISAs, GSK3β kinase activity assays, immunofluorescence, and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…We used 12B2 to examine the regulation of GSK3β by protein phosphatases in cells. We treated HEK cells for 30 min with 10 nM calyculin A, a potent protein phosphatase inhibitor (Ishihara et al, 1989; Resjo et al, 1999), which increases S9 phosphorylation in GSK3β (Morfini et al, 2004; Kim et al, 2009; Xiao et al, 2010). The cell lysates were analyzed in sandwich ELISAs, GSK3β kinase activity assays, immunofluorescence, and western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a feedback regulatory mechanism, this is believed to contribute to fine-tuning of cAMP levels and PKA activity and thereby control of lipolysis. Regarding dephosphorylation and deactivation of PDE3B, PP2A was shown to act as a PDE3B phosphatase ( Resjö et al, 1999 ).…”
Section: Intracellular Brakes On Adipocyte Lipolysismentioning
confidence: 99%
“…We also observed that immunoprecipitation with a phospho-Serine (pSer) 14-3-3 motif antibody pulled down USP43, and importantly, this interaction was hypoxia dependent ( Fig S7B ). Moreover, the interaction between 14-3-3 and USP43 could be replicated using Culyculin A as a phosphatase inhibitor (Resjö et al , 1999), and conversely, prevented by Lambda PP ( Fig S7C ).…”
Section: Resultsmentioning
confidence: 81%